Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.str.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Core Structure of Amyloid Fibrils Formed by Residues 106–126 of the Human Prion Protein

Abstract: Peptides comprising residues 106-126 of the human prion protein (PrP) exhibit many features of the full-length protein. PrP(106-126) induces apoptosis in neurons, forms fibrillar aggregates, and can mediate the conversion of native cellular PrP (PrP(C)) to the scrapie form (PrP(Sc)). Despite a wide range of biochemical and biophysical studies on this peptide, including investigation of its propensity for aggregation, interactions with cell membranes, and PrP-like toxicity, the structure of amyloid fibrils form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
101
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 56 publications
13
101
1
Order By: Relevance
“…We have previously reported the structures of both the amyloid fibrils and nonfibrillar oligomers formed by PrP(106 -126) (37)(38)(39). Here, we confirm that the oligomers are cytotoxic to mammalian cells, and also demonstrate that they exhibit antimicrobial activity.…”
supporting
confidence: 82%
“…We have previously reported the structures of both the amyloid fibrils and nonfibrillar oligomers formed by PrP(106 -126) (37)(38)(39). Here, we confirm that the oligomers are cytotoxic to mammalian cells, and also demonstrate that they exhibit antimicrobial activity.…”
supporting
confidence: 82%
“…Here, it is worth noting that recent studies have suggested similar features in other proteins. For ␤2m and prion proteins, domain-swapped dimers have been observed (19,20), but for both proteins ssNMR and ESR studies on fibrils have indicated an IP sheet structure and a loss of the native conformation (51,(62)(63)(64)(65). Thus, at least in a number of cases, similar observations have been made, when mature fibrils were studied directly.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, this sequence has been found to form amyloid in isolation (21), and structural models for amyloids of several PrP peptides containing this sequence have been presented (22,23,33). In these studies, PrP residues 113-120 have been found to adopt either parallel in-register or antiparallel ␤-structure, with Ala side chains of opposing strands packing into various "steric zippers" as described by Eisenberg and co-workers (34).…”
Section: Essential and Nonessential Regions Of Prp23-144 Amyloidmentioning
confidence: 91%
“…The latter strand contains a species-specific sequence at residues 138 -139 that determines seeding specificity (15,16). The former ␤-strand region, conversely, encompasses a conserved hydrophobic palindrome sequence, 113 AGAAAAGA 120 , which has been shown critical for amyloidogenesis of certain PrP peptides (21)(22)(23) and for propagation of pathological PrP in cell culture (24). However, * This work was supported by National Institutes of Health Grants R01NS038604 and R01NS044158 (to W. K. S.) and R01GM094357 (to C. P.…”
mentioning
confidence: 99%